2018
DOI: 10.5194/angeo-36-555-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar activity and galactic cosmic ray cycles on the modulation of the annual average temperature at two sites in southern Brazil

Abstract: Quasi-periodic variations in solar activity and galactic cosmic rays (GCRs) on decadal and bidecadal timescales have been suggested as a climate forcing mechanism for many regions on Earth. One of these regions is southern Brazil, where the lowest values during the last century were observed for the total geomagnetic field intensity at the Earth's surface. These low values are due to the passage of the center of the South Atlantic Magnetic Anomaly (SAMA), which crosses the Brazilian territory from east to west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…After that period (green points and black fit), the count rate variation and the ratio are in very good agreement with the expectation of a positive radial gradient of about 2.9 % AU −1 (e.g. Vos and Potgieter, 2016;Gieseler and Heber, 2016).…”
Section: Helioradial Gradient Of Cosmic Rayssupporting
confidence: 79%
See 2 more Smart Citations
“…After that period (green points and black fit), the count rate variation and the ratio are in very good agreement with the expectation of a positive radial gradient of about 2.9 % AU −1 (e.g. Vos and Potgieter, 2016;Gieseler and Heber, 2016).…”
Section: Helioradial Gradient Of Cosmic Rayssupporting
confidence: 79%
“…Negative latitudinal gradients have been reported (e.g. Potgieter et al, 2001) but only for a fraction of 1 % •−1 (Gieseler and Heber, 2016). During the comet phase, Rosetta moved from around −7.5 to +7.5 • heliolatitude, which could not account for the decrease in GCR fluxes.…”
Section: Apparent Attenuation Of Galactic Cosmic Ray Flux In the Vicimentioning
confidence: 89%
See 1 more Smart Citation
“…Recent works (e.g. [ 31 , 60 , 61 , 62 , 63 ]) have found interesting correlations between solar and galactic cosmic rays periodic variations and climatic (such as temperature and rainfall) variations in the region where the SAA is located. The entrance of galactic cosmic rays at the atmosphere depends both solar and Earth’s magnetic fields, hence these correlations could also be influenced by a factor depending on the low geomagnetic intensity due to the SAA presence in the region and its continuous increasing for the last centuries.…”
Section: Resultsmentioning
confidence: 99%
“…The negative health implication of some cosmic ray phenomena (e.g ground level enhancement) for airplane crew members is well expected and has been reported by some authors (Matthia et al, 2009;Mishev et al, 2015), and most recently a simulation by Kataoka et al (2015) has suggested that solar energetic particle events without ground level enhancements could even pose significant treats to humans travelling by air. Most recently, Frigo et al (2018) investigated the effect of cosmic rays on climate. They observed that temperature maxima were almost coincident with the maxima of the solar cycle years.…”
Section: Introductionmentioning
confidence: 99%